Lactation Accommodations in the Workplace. Issue 1 (January 2023) - Spatz, Diane L.
Abstract : Lactation accommodations in the workplace are critical for breastfeeding mothers. Without a private room, high-quality pump, and time away from the work environment to pump, continuation of breastfeeding while working is a major challenge. Our breastfeeding expert, Dr. Spatz, presents the recent legislation and policy issues in the United States and suggests ways nurses can advocate to support breastfeeding in the workplace.